The effect of body weight reduction using a lower body positive pressure treadmill on plantar pressure measures while running. (May 2020) - Hodges- Long, Laura; Cross, Kevin; Magrum, Eric; Feger, Mark; Hertel, Jay
Abstract: Objective: To evaluate the effects of body weight reduction at 10% intervals on pressure distribution variables across regions of the foot while running. Study design: Crossover Study Design. Setting: Laboratory. Participants: 12 recreational runners. Main outcome measures: Pressure-time integral, peak pressure, instance of peak pressure, contact area, contact time and center of pressure (COP) location at initial contact across four foot regions were measured while participants ran at self-selected speed on the Lower Body Positive Pressure Treadmill (LBPPT) at 100%, 90%, 80%, 70% and 60% of their body weight (%BW). Results: As the %BW decreased, there were corresponding significant decreases in the pressure-time integral and peak pressures in all four regions of the foot. Significant differences within foot region and %BW for the other variables were infrequent. There was a significant anterior shift of the COP location at initial contact as the %BW decreased. Conclusion: LBPPT is useful for reducing the pressure across the entire foot. Additionally, the anterior translation of the COP location at initial contact with reduced %BW may provide an additional gait retraining tool for prevention and treatment of running injuries as reducing %BW moves the runner away from a rearfoot strike pattern. Highlights: As body weight is reduced, there is a decrease in plantar pressure measures. Decreased body weight may reduce the stress of ambulation to promote healing. Center of pressure at initial contact migrates anterior with decreased body weight. LBPPT may provide a sensory cue to shift footstrike anteriorly for force reduction.